Promosi Bukit Kopi: Harapan dan Tantangan dalam Rangka Persiapan Pengembangan Desa Wisata Bongancina di Bali Utara - Koerniawaty, Francisca Titing; Sudjana, I Made; Pambudi, Bondan (Jurnal Kajian Bali (Journal of Bali Studies), 2022)
This study provides substantial data in designing the coffee hill-based rural tourism development model of Bongancina Village in North Bali. It focused on two objectives firstly, introducing opportunities by supplying the essential data of Bongancina Village’s potencies through tourist attractions identification; secondly, to analyze the challenges that are faced in rural tourism development. This study implemented the initial stages of the R&D approach with a qualitative analysis method. Data collected by using a passive participatory observation, interviews and FGD techniques. The results revealed that it has opportunities to be developed as rural tourism for economic recovery post the Covid-19 pandemic. The 8 criteria of tourist attractions which were classified into 75 indicators were in a feasible position. The challenges identified from the eight criteria can be utilized to determine the strategies in designing a development model. This study result can promote Bongancina Village and enrich the literature for further studies.